2006
DOI: 10.1073/pnas.0600425103
|View full text |Cite
|
Sign up to set email alerts
|

gp130 signaling in proopiomelanocortin neurons mediates the acute anorectic response to centrally applied ciliary neurotrophic factor

Abstract: Ciliary neurotrophic factor (CNTF) exerts anorectic effects by overcoming leptin resistance via activation of hypothalamic neurons. However, the exact site of CNTF action in the hypothalamus has not yet been identified. Using Cre-loxP-mediated recombination in vivo, we have selectively ablated the common cytokine signaling chain gp130, which is required for functional CNTF signaling, in proopiomelanocortin (POMC)-expressing neurons. POMC-specific gp130 knockout mice exhibit unaltered numbers of POMC cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 35 publications
2
43
0
1
Order By: Relevance
“…Indicated tissues were dissected and homogenized in homogenization buffer with a polytron homogenizer (IKA Werke), and Western blot analyses were performed by standard methods with antibodies raised against the respective antibodies as described previously (19,22). HTNC-treated wildtype and PLRG1 flox/flox fibroblasts were directly lysed in 2ϫ sodium dodecyl sulfate (SDS) sample buffer containing 125 mM Tris-HCl (pH 6.8), 5% SDS, 43.5% glycerol, 100 mM dithiothreitol (DTT), and 0.02% bromophenol blue and were heated at 95°C for 5 min.…”
Section: Plrg1mentioning
confidence: 99%
“…Indicated tissues were dissected and homogenized in homogenization buffer with a polytron homogenizer (IKA Werke), and Western blot analyses were performed by standard methods with antibodies raised against the respective antibodies as described previously (19,22). HTNC-treated wildtype and PLRG1 flox/flox fibroblasts were directly lysed in 2ϫ sodium dodecyl sulfate (SDS) sample buffer containing 125 mM Tris-HCl (pH 6.8), 5% SDS, 43.5% glycerol, 100 mM dithiothreitol (DTT), and 0.02% bromophenol blue and were heated at 95°C for 5 min.…”
Section: Plrg1mentioning
confidence: 99%
“…It must be noted, however, that LRb and gp130Rb cannot bind the other's specific ligand; the actions of CNTF are not compromised in the db/db mouse (which lacks the functional LRb; ref. 18), and circulating leptin is normal in brain-specific gp130Rb knockout mice (50). Importantly, gp130R ligands may provide a way to circumvent leptin resistance, because while gp130Rb and LRb have a degree of sequence homology, gp130Rb has multiple tyrosine phosphorylation sites that may allow for adequate signaling in the obese phenotype, in which SOCS proteins are elevated.…”
Section: Figurementioning
confidence: 99%
“…This initial study was confirmed by others, who showed that Axokine ® markedly reduced weight in leptin-resistant rodent models in the absence of side effects such as fever and other metabolic abnormalities associated with cytokine treatment (Kalra et al, 1998;Lambert et al, 2001). While these initial studies demonstrated that CNTF exerted its effects via activation of neurons in the arcuate nuclei of the hypothalamus, it was the work of Brüning and co-workers that delineated the precise central signaling mechanism of CNTF (Janoschek et al, 2006). These authors created a mouse with selective deletion of the gp130R in POMC expressing neurons.…”
Section: Metabolic Actions Of Gp130 Ligandsmentioning
confidence: 81%
“…However, in contrast with littermates expressing gp130 normally, when CNTF was directly administered into the hypothalamus of POMC/gp130R deficient mice it had no effect. This identified the precise neuronal circuit by which CNTF signals in the hypothalamus (Janoschek et al, 2006). It has also been shown that CNTF decreases the activation of AMPK in the hypothalamus, markedly reducing food intake and body weight in animals fed both a chow and high fat diet .…”
Section: Metabolic Actions Of Gp130 Ligandsmentioning
confidence: 88%